2013
DOI: 10.1242/jeb.081067
|View full text |Cite
|
Sign up to set email alerts
|

Environment, behavior and physiology: do birds use barometric pressure to predict storms?

Abstract: SUMMARYSevere storms can pose a grave challenge to the temperature and energy homeostasis of small endothermic vertebrates. Storms are accompanied by lower temperatures and wind, increasing metabolic expenditure, and can inhibit foraging, thereby limiting energy intake. To avoid these potential problems, most endotherms have mechanisms for offsetting the energetic risks posed by storms. One possibility is to use cues to predict oncoming storms and to alter physiology and behavior in ways that make survival mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 56 publications
2
38
0
Order By: Relevance
“…Barometric pressure begins to decline 12-24 h before severe storms (Breuner et al 2013), and Ferruginous Hawks delivered more nest material during these times of below-average barometric pressure, suggesting that they may sense barometric pressure declines and increase nest maintenance behaviours in anticipation of approaching storms. Considering that barometric pressure changes occur hours before visual cues are likely to have appeared, we suggest that it is unlikely that Ferruginous Hawks are responding to a combination of increasing wind speeds, decreasing temperatures, or visual cues such as darkening of the sky as storms approach.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Barometric pressure begins to decline 12-24 h before severe storms (Breuner et al 2013), and Ferruginous Hawks delivered more nest material during these times of below-average barometric pressure, suggesting that they may sense barometric pressure declines and increase nest maintenance behaviours in anticipation of approaching storms. Considering that barometric pressure changes occur hours before visual cues are likely to have appeared, we suggest that it is unlikely that Ferruginous Hawks are responding to a combination of increasing wind speeds, decreasing temperatures, or visual cues such as darkening of the sky as storms approach.…”
Section: Discussionmentioning
confidence: 99%
“…Barometric pressure decreases predictably before severe storms, which some birds can sense (Breuner et al 2013;Metcalfe et al 2013) using sensory hair cells of the inner ear. These sensory hairs move in a fluid matrix inside the paratympanic organ in response to small changes in pressure (von Bartheld and Giannessi 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the general small size and fragile nature of insects the heavy rains and strong winds associated with storms are potentially important mortality factors [11][12]. Thus, adaptations allowing individuals to detect imminent changes in weather conditions would be beneficial and a limited number of studies have shown that insects [13], like mammals [14], birds [15], reptiles [16] and fish [17], modify different behaviours [18][22] in response to the rapid drop in atmospheric pressure (>4 mbars) in the hours preceding a storm [23].…”
Section: Introductionmentioning
confidence: 99%
“…Lefale, 2009;Waiwai and Malsale, 2013;Chand et al, 2014). Examples of weather-related TK include early and more abundant flowering of mango and breadfruit in the harvest season preceding a TC (Whan et al, 2014), the mass movement of birds across a non-native area (Breuner et al, 2013) and changing animal behaviour (Acharya, 2011), indicators that were also mentioned by respondents during the survey. Moller and Berkes (2004) discuss how utilising qualitative TK data and quantitative scientific knowledge (SK) can benefit and improve our knowledge in many ways (summarised in Table 4).…”
Section: Improving Adaptation Practices For Small Island States (Sissmentioning
confidence: 99%